Subjective Cognitive Impairment Is a Predominantly Benign Condition in Memory Clinic Patients Followed for 6 Years: The Gothenburg-Oslo MCI Study - Hessen, Erik (Dement Geriatr Cogn Dis Extra, 2017)
BACKGROUND/AIMS: In the quest for prevention or treatment, there is a need to find early markers for preclinical dementia. This study observed memory clinic patients with subjective cognitive impairment (SCI) and normal cognitive function at baseline. The primary aim was to address SCI as a potential risk factor for cognitive decline. The secondary aim was to address a potential relation between (1) baseline cerebrospinal fluid biomarkers and (2) a decline in memory performance over the first 2 years of follow-up, with a possible cognitive decline after 6 years. METHODS: Eighty-one patients (mean age 61 years) were recruited from university memory clinics and followed up for 6 years. RESULTS: Eighty-six percent of the cohort remained cognitively stable or improved, 9% developed mild cognitive impairment, and only 5% (n = 4) developed dementia. Regression analysis revealed that low levels of Aβ(42) at baseline and memory decline during the first 2 years predicted dementia. When combined, these variables were associated with a 50% risk of developing dementia. CONCLUSIONS: Cognitive stability for 86% of the cohort suggests that SCI is predominantly a benign condition with regard to neuropathology. The low number of individuals who developed dementia limits the generalizability of the results and discussion of progression factors.